Really, health is but just a business - Abd Razak, Dzulkifli (2008)
AT the slightest hint to separate prescribing from the dispensing of medicines, the healthcare fraternity is at each other's throat once again. Perhaps it is an "epic battle", considering this issue has dragged on unresolved for three decades. The same tired arguments are being rehearsed again. What seems clear is that the issue is beyond just professional considerations. Rather, it is a complicated mixture of economics as well as politics; health is just an incidental part of the argument.